A new digital signature scheme with message recovery using hybrid problems - Nedal Tahat; Rania Shaqboua; Emad E. Abdallah; Mohammad Bsoul; Wasfi Shatanawi (Institute of Advanced Engineering and Science, 2019)
We present a new digital signature scheme with message recovery and its authenticated encryption based on elliptic curve discrete logarithm and quadratic residue. The main idea is to provide a higher level of security than all other techniques that use signatures with single hard problem including factoring, discrete logarithm, residuosity, or elliptic curves. The proposed digital signature schemes do not involve any modular exponentiation operations that leave no gap for attackers. The security analysis demonstrates the improved performance of the proposed schemes in comparison with existing techniques in terms of the ability to resist the most common attacks